Advertisement Remove all ads

Solve for x : (2x)/(x-3)+1/(2x+3)+(3x+9)/((x-3)(2x+3)) = 0, x!=3 - Mathematics

Advertisement Remove all ads
Advertisement Remove all ads
Advertisement Remove all ads

Solve for x

`(2x)/(x-3)+1/(2x+3)+(3x+9)/((x-3)(2x+3)) = 0, x!=3,`

Advertisement Remove all ads

Solution

Given:

`(2x)/(x-3)+1/(2x+3)+(3x+9)/((x-3)(2x+3))=0`

`=>(2x(2x+3)+(x-3)+3x+9)/((x-3)(2x+3))=0`

⇒ 4x2+6x+x3+3x+9=0

⇒ 4x2+10x+6=0

⇒ 4x2+4x+6x+6=0

⇒ 4x(x+1)+6(x+1)=0

(x+1)(4x+6)=0

x+1=0  or 4x+6=0

`=>x=-1,-3/2`

But 

`x !=-3/2`

Thus, x=1 is the solution of the given equation.

Concept: Solutions of Quadratic Equations by Factorization
  Is there an error in this question or solution?
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×